Wear-resistant titanium-aluminum alloy material and preparation method thereof
Patent Information
- Application Number
- CN202611203973.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0002]钛铝合金因比强度高、耐高温,广泛应用于航空发动机、高端机械耐磨部件,但常规钛铝合金硬度低、耐磨性能差,且断裂韧性不足,易在磨损过程中发生脆性断裂
本发明将先以钛铝铌预合金粉末为基体,与正硅酸乙酯、乙酰丙酮钨、硼酸三甲酯、乙醇铌及无水丙酸混合,经非水解溶胶-凝胶法得到前驱体溶胶,经真空搅拌喷涂、两步活化气氛煅烧得到稳定膜层后,喷涂葡萄糖溶液,再通过分段反应真空热压烧结,以实现优异断裂韧性与耐磨性的效果。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium-aluminum alloy materials technology, specifically to a wear-resistant titanium-aluminum alloy material and its preparation method. Background Technology
[0002] Titanium-aluminum alloys are widely used in aero-engines and high-end mechanical wear-resistant components due to their high specific strength and high temperature resistance. However, conventional titanium-aluminum alloys have low hardness, poor wear resistance, and insufficient fracture toughness, making them prone to brittle fracture during wear. Existing modification processes often use the hydrolysis sol-gel method to introduce the reinforcing phase, which easily leads to precursor agglomeration, resulting in uneven reinforcing phase composition and poor consistency in wear resistance. Rapid heating during calcination and debinding can easily cause film cracking, forming coating defects that lead to uneven subsequent reactions. Unreduced oxide impurities can easily become crack initiation sites, and continuous brittle alumina phases at grain boundaries can significantly reduce the material's fracture toughness. A single reinforcement method cannot simultaneously achieve wear resistance strengthening and toughening. Existing processes cannot achieve synergistic optimization of reinforcing phase homogenization, defect elimination, and grain boundary modification, making it difficult to meet the service requirements of high-end wear-resistant components. Summary of the Invention
[0003] The purpose of this invention is to provide a wear-resistant titanium-aluminum alloy material and its preparation method, so as to solve the problems existing in the prior art.
[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a wear-resistant titanium-aluminum alloy material, comprising the following steps: (1) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethanol and organic solvent A are mixed in a mass ratio of 1.5~2:0.5~1:0.8~1:0.5~0.6:10, and then 0.4~0.6 times the mass of tetraethyl orthosilicate stabilizer is added. The mixture is stirred at room temperature for 30 min to form solution A. At the same time, organic solvent B is dissolved in organic solvent A in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under vigorous stirring, solution B is slowly added dropwise to solution A. After the addition is complete, the mixture is placed in a 40℃ water bath and stirred for 2 h to obtain a homogeneous precursor sol. (2) The pretreated titanium-aluminum pre-alloyed powder was placed in an argon atmosphere. The precursor sol, which was 2 to 3 times the mass of the titanium-aluminum pre-alloyed powder, was mixed with the powder spraying in three separate times. A uniform amorphous precursor gel film was built on the surface of each powder in a layer-by-layer accumulation manner. The powder was spread out and calcined in two steps. After cooling in the furnace, the self-made powder was obtained. (3) The self-made powder was sprayed into the self-made glucose solution under argon protection and slow stirring, stirred for 15 min, and vacuum dried at 60℃ for 2 h to obtain the self-made composite powder containing the carbon source precursor layer. It was loaded into a mold, pre-pressed into a blank, and calcined in a two-step activation atmosphere to obtain wear-resistant titanium-aluminum alloy material.
[0005] Furthermore, the organic solvent A mentioned in step (1) is anhydrous ethanol.
[0006] Furthermore, the stabilizer in step (1) is acetylacetone.
[0007] Furthermore, the organic solvent B mentioned in step (1) is anhydrous propionic acid.
[0008] Furthermore, the slow dripping rate in step (1) is 2 drops / s.
[0009] Furthermore, the thickness of the amorphous precursor gel film in step (2) is 300~400nm.
[0010] Furthermore, the tiling thickness in step (2) is 5 mm.
[0011] Furthermore, the homemade glucose solution in step (3) is prepared by weighing 5g of glucose and dissolving it in 50mL of deionized water, stirring magnetically until completely dissolved, and preparing a glucose aqueous solution with a mass fraction of 9%.
[0012] Furthermore, the carbon source precursor layer in step (3) is a carbon source precursor layer with a thickness of 10 nm.
[0013] Furthermore, the mold in step (3) is a high-strength graphite mold with a boron nitride release agent uniformly coated on the inner wall.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention first uses titanium-aluminum-niobium pre-alloyed powder as a matrix, mixes it with tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethanol, and anhydrous propionic acid, and obtains a precursor sol through a non-hydrolytic sol-gel method. After obtaining a stable film layer through vacuum stirring spraying and two-step activation atmosphere calcination, a glucose solution is sprayed on, and then the film is sintered by segmented reaction vacuum hot pressing to achieve excellent fracture toughness and wear resistance.
[0015] This invention first uses titanium-aluminum-niobium pre-alloyed powder as a matrix, which is mixed with tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethoxide, and anhydrous propionic acid. A precursor sol is obtained via a non-hydrolyzed sol-gel method. After vacuum stirring and spraying, and two-step calcination in an activated atmosphere to obtain a stable film, a glucose solution is sprayed on, followed by segmented reaction vacuum hot pressing sintering to obtain the titanium-aluminum alloy material. The uniform precursor sol avoids the agglomeration caused by traditional hydrolysis methods, ensuring the uniform composition of the subsequently generated high-entropy silicide reinforcing phase, resulting in good and consistent wear resistance. The extremely slow heating and low-temperature debinding during the two-step calcination in an activated atmosphere prevents film cracking, eliminates coating defects on the powder surface, provides a uniform coating substrate for the subsequent carbon sacrificial layer, and avoids uneven subsequent reactions. Secondly, the inert activation process preserves the amorphous state of the oxide, eliminating crack sources caused by unreduced oxide impurities and improving the fracture toughness of the material. The carbon layer formed by the synergistic segmented reaction vacuum hot pressing sintering with glucose solution coating preferentially and completely reduces tungsten oxide to metallic tungsten, and simultaneously converts the aluminothermic reduction products into aluminum nitride nanoparticles through carbothermic reaction, eliminating the continuous brittle layer of aluminum oxide on the grain boundaries. It also has the toughening effect of pinning grain boundaries and hindering crack propagation, further improving the fracture toughness of the material. At the same time, high-entropy silicides interconnect along the grain boundaries to form a load-bearing skeleton and guide titanium boride to grow into whiskers along specific crystal directions of the matrix. The two work together to effectively resist the plowing of abrasive particles, strengthen the shear resistance of micro-areas, and endow the material with excellent wear resistance. Detailed Implementation
[0016] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] To more clearly illustrate the method provided by the present invention, the following embodiments are provided, in which the testing methods for various properties of the titanium-aluminum alloy material produced are as follows: Fracture toughness test method: The alloy materials prepared in Examples 1-5 and Comparative Examples 1-5 were tested in accordance with the standard GB / T 4161-2007 "Metallic Materials Plane Strain Fracture Toughness Test Method".
[0018] Wear resistance test method: The alloy materials prepared in Examples 1-5 and Comparative Examples 1-5 were tested in accordance with the standard GB / T 12444.2-2018 "Metallic Materials Wear Test Methods - Ring and Block Wear Test". Example 1
[0019] (1) Take 100g of titanium-aluminum-niobium pre-alloyed powder according to the mass ratio of titanium 50%, aluminum 45%, and niobium 5%, pass it through 200 mesh and 325 mesh standard sieves in sequence, and cut the intermediate fraction with a particle size range of 50µm to ensure that the movement behavior of each particle is consistent during the subsequent fluidized coating process, so as to obtain a coating layer with uniform thickness. Dry it at 120℃ for 4h to completely remove the surface adsorbed water to obtain the pretreated titanium-aluminum-niobium pre-alloyed powder. (2) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethoxide and anhydrous ethanol were mixed in a mass ratio of 1.5:0.5:0.8:0.5:10. Then, acetylacetone was added in a mass ratio of 0.4 times that of tetraethyl orthosilicate as a stabilizer to prevent the precipitation of tungsten acetylacetone. The mixture was stirred at 300 rpm for 30 min at room temperature to form a clear and uniform solution A. At the same time, anhydrous propionic acid was dissolved in anhydrous ethanol in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under a stirring speed of 1000 rpm, solution B was slowly added to solution A at a rate of 2 drops / s. After the addition was completed, the mixture was placed in a 40℃ water bath and stirred at 500 rpm for 2 h to allow the non-hydrolytic condensation reaction catalyzed by anhydrous propionic acid to proceed fully, and a homogeneous precursor sol was obtained. (3) Place 100g of titanium-aluminum pre-alloy powder from step (1) under an argon atmosphere, and mix the precursor sol with the powder in three equal parts by two times the mass of the titanium-aluminum pre-alloy powder. After each spraying, stir continuously at 50rpm for 15min. Then dry for 30min at a temperature of 40℃ and a vacuum of -0.09 MPa. Build a uniform amorphous precursor gel film on the surface of each powder in a layer-by-layer accumulation manner. The final total film thickness is controlled at 300nm. After coating, the powder is spread evenly with a layer thickness of 5 mm and subjected to two-step calcination: the first step is to raise the temperature to 250°C at an extremely slow heating rate of 0.5°C / min under a flowing air atmosphere with a flow rate of 100 mL / min and hold it for 2 hours to allow the organic matter to be fully oxidized and decomposed and the gas to escape steadily; the second step is to switch to a flowing high-purity argon atmosphere with a flow rate of 100 mL / min, raise the temperature to 450°C at a rate of 2°C / min and hold it for 1 hour to stabilize the amorphous structure. After cooling with the furnace, a self-made powder with an amorphous mixed oxide film on the surface is obtained. (4) Weigh 5g of glucose and dissolve it in 50mL of deionized water. Stir magnetically until completely dissolved to prepare a 9% glucose aqueous solution. Place the self-made powder back into a vacuum stirring dryer. Under argon protection and stirring at 40rpm, spray the glucose solution in one go and stir for 15min to uniformly wet the surface of each powder particle. Then dry for 2h under a jacket temperature of 60℃ and a vacuum degree of -0.09 MPa to allow the moisture to evaporate slowly. Glucose is uniformly precipitated on the surface of the oxide film to form a carbon source precursor layer with a thickness of 10nm, thus obtaining the self-made composite powder. (5) The self-made composite powder was loaded into a high-strength graphite mold with a boron nitride release agent evenly coated on the inner wall, and pre-pressed into a blank at a pressure of 200 MPa on a cold isostatic press. The mold was then placed in a vacuum hot pressing sintering furnace and evacuated to a pressure better than 5 × 10⁻⁶ MPa. -3 Pa. The sintering process is divided into five stages: the first stage involves heating from room temperature to 600℃ at a rate of 5℃ / min, applying only contact pressure; the second stage involves heating from 600℃ to 900℃ at a rate of 1℃ / min, with the pressure increasing to 10MPa. This slow heating range provides sufficient time for the carbothermic reduction reaction, allowing carbon to preferentially and completely reduce tungsten oxide to metallic tungsten and convert aluminum oxide to aluminum nitride, with the generated carbon monoxide gas escaping smoothly; the third stage involves holding at 900℃ for 1 hour while maintaining a pressure of 10MPa to ensure the complete reduction reaction; the fourth stage... The temperature was increased from 900℃ to 1100℃ at a rate of 5℃ / min, and the pressure was increased to 20MPa, at which point the billet began to densify initially. In the fifth stage, the temperature was increased from 1100℃ to 1300℃ at a rate of 5℃ / min, and the pressure was gradually increased to 45MPa. The billet was held at 1300℃ and 45MPa for 2 hours. During this stage, high-entropy silicides were generated in situ along the original powder boundaries and interconnected to form a three-dimensional network framework. Boron atoms rapidly diffused into the grains and directionally grew titanium boride whiskers, forming an interlocking structure of grain boundary framework and intragranular whiskers, while simultaneously completing full densification. After the holding period, the furnace was cooled. When the temperature dropped below 800℃, the pressure was unloaded to obtain a wear-resistant titanium-aluminum alloy material. Example 2
[0020] (1) Take 100g of titanium-aluminum-niobium pre-alloyed powder according to the mass ratio of titanium 50%, aluminum 45%, and niobium 5%, pass it through 200 mesh and 325 mesh standard sieves in sequence, and cut the intermediate fraction with a particle size range of 50~150µm to ensure that the movement behavior of each particle is consistent during the subsequent fluidized coating process, so as to obtain a coating layer with uniform thickness. Dry it at 120℃ for 4h to completely remove the surface adsorbed water to obtain the pretreated titanium-aluminum-niobium pre-alloyed powder. (2) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethoxide and anhydrous ethanol were mixed in a mass ratio of 1.6:0.6:0.85:0.52:10. Then, acetylacetone was added in a mass ratio of 0.45 times that of tetraethyl orthosilicate as a stabilizer to prevent the precipitation of tungsten acetylacetone. The mixture was stirred at 300 rpm for 30 min at room temperature to form a clear and uniform solution A. At the same time, anhydrous propionic acid was dissolved in anhydrous ethanol in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under stirring at 1000 rpm, solution B was slowly added to solution A at a rate of 2 drops / s. After the addition was completed, the mixture was placed in a 40℃ water bath and stirred at 500 rpm for 2 h to allow the non-hydrolytic condensation reaction catalyzed by anhydrous propionic acid to proceed fully, and a homogeneous precursor sol was obtained. (3) Place 100g of titanium-aluminum pre-alloy powder from step (1) under an argon atmosphere, and mix the precursor sol with the powder in three equal parts with 2.2 times the mass of the titanium-aluminum pre-alloy powder in three separate sprays. After each spraying, stir continuously at 50rpm for 15min. Then dry for 30min at a temperature of 40℃ and a vacuum of -0.09 MPa. Build a uniform amorphous precursor gel film on the surface of each powder in a layer-by-layer accumulation manner. The final total film thickness is controlled at 320nm. After coating, the powder is spread evenly with a layer thickness of 5 mm and subjected to two-step calcination: the first step is to raise the temperature to 250°C at an extremely slow heating rate of 0.5°C / min under a flowing air atmosphere with a flow rate of 100 mL / min and hold it for 2 hours to allow the organic matter to be fully oxidized and decomposed and the gas to escape steadily; the second step is to switch to a flowing high-purity argon atmosphere with a flow rate of 100 mL / min, raise the temperature to 450°C at a rate of 2°C / min and hold it for 1 hour to stabilize the amorphous structure. After cooling with the furnace, a self-made powder with an amorphous mixed oxide film on the surface is obtained. (4) Weigh 5g of glucose and dissolve it in 50mL of deionized water. Stir magnetically until completely dissolved to prepare a 9% glucose aqueous solution. Place the self-made powder back into a vacuum stirring dryer. Under argon protection and stirring at 40rpm, spray the glucose solution in one go and stir for 15min to uniformly wet the surface of each powder particle. Then dry for 2h under a jacket temperature of 60℃ and a vacuum degree of -0.09 MPa to allow the moisture to evaporate slowly. Glucose is uniformly precipitated on the surface of the oxide film to form a carbon source precursor layer with a thickness of 10nm, thus obtaining the self-made composite powder. (5) The self-made composite powder was loaded into a high-strength graphite mold with a boron nitride release agent evenly coated on the inner wall, and pre-pressed into a blank at a pressure of 200 MPa on a cold isostatic press. The mold was then placed in a vacuum hot pressing sintering furnace and evacuated to a pressure better than 5 × 10⁻⁶ MPa. -3Pa. The sintering process is divided into five stages: the first stage involves heating from room temperature to 600℃ at a rate of 5℃ / min, applying only contact pressure; the second stage involves heating from 600℃ to 900℃ at a rate of 1℃ / min, with the pressure increasing to 10MPa. This slow heating range provides sufficient time for the carbothermic reduction reaction, allowing carbon to preferentially and completely reduce tungsten oxide to metallic tungsten and convert aluminum oxide to aluminum nitride, with the generated carbon monoxide gas escaping smoothly; the third stage involves holding at 900℃ for 1 hour while maintaining a pressure of 10MPa to ensure the complete reduction reaction; the fourth stage... The temperature was increased from 900℃ to 1100℃ at a rate of 5℃ / min, and the pressure was increased to 20MPa, at which point the billet began to densify initially. In the fifth stage, the temperature was increased from 1100℃ to 1300℃ at a rate of 5℃ / min, and the pressure was gradually increased to 45MPa. The billet was held at 1300℃ and 45MPa for 2 hours. During this stage, high-entropy silicides were generated in situ along the original powder boundaries and interconnected to form a three-dimensional network framework. Boron atoms rapidly diffused into the grains and directionally grew titanium boride whiskers, forming an interlocking structure of grain boundary framework and intragranular whiskers, while simultaneously completing full densification. After the holding period, the furnace was cooled. When the temperature dropped below 800℃, the pressure was unloaded to obtain a wear-resistant titanium-aluminum alloy material. Example 3
[0021] (1) Take 100g of titanium-aluminum-niobium pre-alloyed powder according to the mass ratio of titanium 50%, aluminum 45%, and niobium 5%, pass it through 200 mesh and 325 mesh standard sieves in sequence, and cut the intermediate fraction with a particle size range of 50~150µm to ensure that the movement behavior of each particle is consistent during the subsequent fluidized coating process, so as to obtain a coating layer with uniform thickness. Dry it at 120℃ for 4h to completely remove the surface adsorbed water to obtain the pretreated titanium-aluminum-niobium pre-alloyed powder. (2) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethoxide and anhydrous ethanol were mixed in a mass ratio of 1.75:0.85:0.9:0.55:10. Then, acetylacetone was added in a mass ratio of 0.5 times that of tetraethyl orthosilicate as a stabilizer to prevent the precipitation of tungsten acetylacetone. The mixture was stirred at 300 rpm for 30 min at room temperature to form a clear and uniform solution A. At the same time, anhydrous propionic acid was dissolved in anhydrous ethanol in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under a stirring speed of 1000 rpm, solution B was slowly added to solution A at a rate of 2 drops / s. After the addition was completed, the mixture was placed in a 40°C water bath and stirred at 500 rpm for 2 h to allow the non-hydrolytic condensation reaction catalyzed by anhydrous propionic acid to proceed fully, and a homogeneous precursor sol was obtained. (3) Place 100g of titanium-aluminum pre-alloy powder from step (1) under an argon atmosphere, and mix the precursor sol with the powder in three equal parts with 2.5 times the mass of the titanium-aluminum pre-alloy powder. After each spraying, stir continuously at 50rpm for 15min. Then dry for 30min at a temperature of 40℃ and a vacuum of -0.09 MPa. Build a uniform amorphous precursor gel film on the surface of each powder in a layer-by-layer accumulation manner. The final total film thickness is controlled at 350nm. After coating, the powder is spread evenly with a layer thickness of 5 mm and subjected to two-step calcination: the first step is to raise the temperature to 250°C at an extremely slow heating rate of 0.5°C / min under a flowing air atmosphere with a flow rate of 100 mL / min and hold it for 2 hours to allow the organic matter to be fully oxidized and decomposed and the gas to escape steadily; the second step is to switch to a flowing high-purity argon atmosphere with a flow rate of 100 mL / min, raise the temperature to 450°C at a rate of 2°C / min and hold it for 1 hour to stabilize the amorphous structure. After cooling with the furnace, a self-made powder with an amorphous mixed oxide film on the surface is obtained. (4) Weigh 5g of glucose and dissolve it in 50mL of deionized water. Stir magnetically until completely dissolved to prepare a 9% glucose aqueous solution. Place the self-made powder back into a vacuum stirring dryer. Under argon protection and stirring at 40rpm, spray the glucose solution in one go and stir for 15min to uniformly wet the surface of each powder particle. Then dry for 2h under a jacket temperature of 60℃ and a vacuum degree of -0.09 MPa to allow the moisture to evaporate slowly. Glucose is uniformly precipitated on the surface of the oxide film to form a carbon source precursor layer with a thickness of 10nm, thus obtaining the self-made composite powder. (5) The self-made composite powder was loaded into a high-strength graphite mold with a boron nitride release agent evenly coated on the inner wall, and pre-pressed into a blank at a pressure of 200 MPa on a cold isostatic press. The mold was then placed in a vacuum hot pressing sintering furnace and evacuated to a pressure better than 5 × 10⁻⁶ MPa. -3Pa. The sintering process is divided into five stages: the first stage involves heating from room temperature to 600℃ at a rate of 5℃ / min, applying only contact pressure; the second stage involves heating from 600℃ to 900℃ at a rate of 1℃ / min, with the pressure increasing to 10MPa. This slow heating range provides sufficient time for the carbothermic reduction reaction, allowing carbon to preferentially and completely reduce tungsten oxide to metallic tungsten and convert aluminum oxide to aluminum nitride, with the generated carbon monoxide gas escaping smoothly; the third stage involves holding at 900℃ for 1 hour while maintaining a pressure of 10MPa to ensure the complete reduction reaction; the fourth stage... The temperature was increased from 900℃ to 1100℃ at a rate of 5℃ / min, and the pressure was increased to 20MPa, at which point the billet began to densify initially. In the fifth stage, the temperature was increased from 1100℃ to 1300℃ at a rate of 5℃ / min, and the pressure was gradually increased to 45MPa. The billet was held at 1300℃ and 45MPa for 2 hours. During this stage, high-entropy silicides were generated in situ along the original powder boundaries and interconnected to form a three-dimensional network framework. Boron atoms rapidly diffused into the grains and directionally grew titanium boride whiskers, forming an interlocking structure of grain boundary framework and intragranular whiskers, while simultaneously completing full densification. After the holding period, the furnace was cooled. When the temperature dropped below 800℃, the pressure was unloaded to obtain a wear-resistant titanium-aluminum alloy material. Example 4
[0022] (1) Take 100g of titanium-aluminum-niobium pre-alloyed powder according to the mass ratio of titanium 50%, aluminum 45%, and niobium 5%, pass it through 200 mesh and 325 mesh standard sieves in sequence, and cut the intermediate fraction with a particle size range of 50~150µm to ensure that the movement behavior of each particle is consistent during the subsequent fluidized coating process, so as to obtain a coating layer with uniform thickness. Dry it at 120℃ for 4h to completely remove the surface adsorbed water to obtain the pretreated titanium-aluminum-niobium pre-alloyed powder. (2) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethoxide and anhydrous ethanol were mixed in a mass ratio of 1.9:0.9:0.95:0.58:10. Then, acetylacetone was added in a mass ratio of 0.55 times that of tetraethyl orthosilicate as a stabilizer to prevent the precipitation of tungsten acetylacetone. The mixture was stirred at 300 rpm for 30 min at room temperature to form a clear and uniform solution A. At the same time, anhydrous propionic acid was dissolved in anhydrous ethanol in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under a stirring speed of 1000 rpm, solution B was slowly added to solution A at a rate of 2 drops / s. After the addition was completed, the mixture was placed in a 40°C water bath and stirred at 500 rpm for 2 h to allow the non-hydrolysis condensation reaction catalyzed by anhydrous propionic acid to proceed fully, and a homogeneous precursor sol was obtained. (3) Place 100g of titanium-aluminum pre-alloy powder from step (1) under an argon atmosphere, and mix the precursor sol with the powder in three equal parts with 2.8 times the mass of the titanium-aluminum pre-alloy powder. After each spraying, stir continuously at 50rpm for 15min. Then dry for 30min at a temperature of 40℃ and a vacuum of -0.09 MPa. Build a uniform amorphous precursor gel film on the surface of each powder in a layer-by-layer accumulation manner. The final total film thickness is controlled at 380nm. After coating, the powder is spread evenly with a layer thickness of 5 mm and subjected to two-step calcination: the first step is to raise the temperature to 250°C at an extremely slow heating rate of 0.5°C / min under a flowing air atmosphere with a flow rate of 100 mL / min and hold it for 2 hours to allow the organic matter to be fully oxidized and decomposed and the gas to escape steadily; the second step is to switch to a flowing high-purity argon atmosphere with a flow rate of 100 mL / min, raise the temperature to 450°C at a rate of 2°C / min and hold it for 1 hour to stabilize the amorphous structure. After cooling with the furnace, a self-made powder with an amorphous mixed oxide film on the surface is obtained. (4) Weigh 5g of glucose and dissolve it in 50mL of deionized water. Stir magnetically until completely dissolved to prepare a 9% glucose aqueous solution. Place the self-made powder back into a vacuum stirring dryer. Under argon protection and stirring at 40rpm, spray the glucose solution in one go and stir for 15min to uniformly wet the surface of each powder particle. Then dry for 2h under a jacket temperature of 60℃ and a vacuum degree of -0.09 MPa to allow the moisture to evaporate slowly. Glucose is uniformly precipitated on the surface of the oxide film to form a carbon source precursor layer with a thickness of 10nm, thus obtaining the self-made composite powder. (5) The self-made composite powder was loaded into a high-strength graphite mold with a boron nitride release agent evenly coated on the inner wall, and pre-pressed into a blank at a pressure of 200 MPa on a cold isostatic press. The mold was then placed in a vacuum hot pressing sintering furnace and evacuated to a pressure better than 5 × 10⁻⁶ MPa. -3Pa. The sintering process is divided into five stages: the first stage involves heating from room temperature to 600℃ at a rate of 5℃ / min, applying only contact pressure; the second stage involves heating from 600℃ to 900℃ at a rate of 1℃ / min, with the pressure increasing to 10MPa. This slow heating range provides sufficient time for the carbothermic reduction reaction, allowing carbon to preferentially and completely reduce tungsten oxide to metallic tungsten and convert aluminum oxide to aluminum nitride, with the generated carbon monoxide gas escaping smoothly; the third stage involves holding at 900℃ for 1 hour while maintaining a pressure of 10MPa to ensure the complete reduction reaction; the fourth stage... The temperature was increased from 900℃ to 1100℃ at a rate of 5℃ / min, and the pressure was increased to 20MPa, at which point the billet began to densify initially. In the fifth stage, the temperature was increased from 1100℃ to 1300℃ at a rate of 5℃ / min, and the pressure was gradually increased to 45MPa. The billet was held at 1300℃ and 45MPa for 2 hours. During this stage, high-entropy silicides were generated in situ along the original powder boundaries and interconnected to form a three-dimensional network framework. Boron atoms rapidly diffused into the grains and directionally grew titanium boride whiskers, forming an interlocking structure of grain boundary framework and intragranular whiskers, while simultaneously completing full densification. After the holding period, the furnace was cooled. When the temperature dropped below 800℃, the pressure was unloaded to obtain a wear-resistant titanium-aluminum alloy material. Example 5
[0023] (1) Take 100g of titanium-aluminum-niobium pre-alloyed powder according to the mass ratio of titanium 50%, aluminum 45%, and niobium 5%, pass it through 200 mesh and 325 mesh standard sieves in sequence, and cut the intermediate fraction with a particle size range of 50~150µm to ensure that the movement behavior of each particle is consistent during the subsequent fluidized coating process, so as to obtain a coating layer with uniform thickness. Dry it at 120℃ for 4h to completely remove the surface adsorbed water to obtain the pretreated titanium-aluminum-niobium pre-alloyed powder. (2) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethoxide and anhydrous ethanol were mixed in a mass ratio of 2:1:1:0.6:10. Then, acetylacetone with a mass of 0.6 times that of tetraethyl orthosilicate was added as a stabilizer to prevent the precipitation of tungsten acetylacetone. The mixture was stirred at 300 rpm for 30 min at room temperature to form a clear and uniform solution A. At the same time, anhydrous propionic acid was dissolved in anhydrous ethanol in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under stirring at 1000 rpm, solution B was slowly added to solution A at a rate of 2 drops / s. After the addition was completed, the mixture was placed in a 40℃ water bath and stirred at 500 rpm for 2 h to allow the non-hydrolytic condensation reaction catalyzed by anhydrous propionic acid to proceed fully, and a homogeneous precursor sol was obtained. (3) Place 100g of titanium-aluminum pre-alloy powder from step (1) under an argon atmosphere, and mix the precursor sol, which is 3 times the mass of the titanium-aluminum pre-alloy powder, with the powder in three equal parts. After each spraying, stir continuously at 50rpm for 15min. Then dry for 30min at a temperature of 40℃ and a vacuum of -0.09 MPa. Build a uniform amorphous precursor gel film on the surface of each powder in a layer-by-layer accumulation manner. The final total film thickness is controlled at 400nm. After coating, the powder is spread evenly with a layer thickness of 5 mm and subjected to two-step calcination: the first step is to raise the temperature to 250°C at an extremely slow heating rate of 0.5°C / min under a flowing air atmosphere with a flow rate of 100 mL / min and hold it for 2 hours to allow the organic matter to be fully oxidized and decomposed and the gas to escape steadily; the second step is to switch to a flowing high-purity argon atmosphere with a flow rate of 100 mL / min, raise the temperature to 450°C at a rate of 2°C / min and hold it for 1 hour to stabilize the amorphous structure. After cooling with the furnace, a self-made powder with an amorphous mixed oxide film on the surface is obtained. (4) Weigh 5g of glucose and dissolve it in 50mL of deionized water. Stir magnetically until completely dissolved to prepare a 9% glucose aqueous solution. Place the self-made powder back into a vacuum stirring dryer. Under argon protection and stirring at 40rpm, spray the glucose solution in one go and stir for 15min to uniformly wet the surface of each powder particle. Then dry for 2h under a jacket temperature of 60℃ and a vacuum degree of -0.09 MPa to allow the moisture to evaporate slowly. Glucose is uniformly precipitated on the surface of the oxide film to form a carbon source precursor layer with a thickness of 10nm, thus obtaining the self-made composite powder. (5) The self-made composite powder was loaded into a high-strength graphite mold with a boron nitride release agent evenly coated on the inner wall, and pre-pressed into a blank at a pressure of 200 MPa on a cold isostatic press. The mold was then placed in a vacuum hot pressing sintering furnace and evacuated to a pressure better than 5 × 10⁻⁶ MPa. -3Pa. The sintering process is divided into five stages: the first stage involves heating from room temperature to 600℃ at a rate of 5℃ / min, applying only contact pressure; the second stage involves heating from 600℃ to 900℃ at a rate of 1℃ / min, with the pressure increasing to 10MPa. This slow heating range provides sufficient time for the carbothermic reduction reaction, allowing carbon to preferentially and completely reduce tungsten oxide to metallic tungsten and convert aluminum oxide to aluminum nitride, with the generated carbon monoxide gas escaping smoothly; the third stage involves holding at 900℃ for 1 hour while maintaining a pressure of 10MPa to ensure the complete reduction reaction; the fourth stage... The temperature was increased from 900℃ to 1100℃ at a rate of 5℃ / min, and the pressure was increased to 20MPa, at which point the billet began to densify initially. In the fifth stage, the temperature was increased from 1100℃ to 1300℃ at a rate of 5℃ / min, and the pressure was gradually increased to 45MPa. The billet was held at 1300℃ and 45MPa for 2 hours. During this stage, high-entropy silicides were generated in situ along the original powder boundaries and interconnected to form a three-dimensional network framework. Boron atoms rapidly diffused into the grains and directionally grew titanium boride whiskers, forming an interlocking structure of grain boundary framework and intragranular whiskers, while simultaneously completing full densification. After the holding period, the furnace was cooled. When the temperature dropped below 800℃, the pressure was unloaded to obtain a wear-resistant titanium-aluminum alloy material.
[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that steps (2), (3), and (4) are omitted, and the pre-treated titanium-aluminum-niobium pre-alloyed powder from step (1) is used instead of the self-made composite powder for step (5).
[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that the titanium-aluminum-niobium pre-alloyed powder is not pretreated, while the other steps are the same as in Example 3.
[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that steps (2) and (3) are omitted, and step (4) is changed to: weigh 5g of glucose and dissolve it in 50mL of deionized water, stir magnetically until completely dissolved, and prepare a glucose aqueous solution with a mass fraction of 9%. The pretreated titanium-aluminum-niobium pre-alloy powder is placed back into a vacuum stirring dryer, and under argon protection and stirring at 40rpm, the glucose solution is sprayed in at one time and stirred for 15min to uniformly wet the surface of each powder particle. Then, it is dried for 2h under the conditions of jacket temperature of 60℃ and vacuum degree of -0.09MPa to allow the moisture to evaporate slowly, and glucose is uniformly precipitated on the surface of the oxide film to form a carbon source precursor layer with a thickness of 10nm, thus obtaining the self-made composite powder. The remaining steps are the same as in Example 3.
[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that step (4) is omitted, while the remaining steps are the same as in Example 3.
[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that the two-step calcination in an activating atmosphere is not used; instead, conventional sintering is used. The remaining steps are the same as in Example 3.
[0029] Example of effect Table 1 below shows the performance analysis results of the titanium-aluminum alloy materials of Examples 1 to 5 and Comparative Examples 1 to 5 of the present invention.
[0030] Table 1
[0031] Comparison of experimental data on fracture toughness between the examples and comparative examples reveals that the extremely slow heating and low-temperature debinding during the two-step activation atmosphere calcination in this invention prevents film cracking, eliminates coating defects on the powder surface, provides a uniform coating substrate for the subsequent carbon sacrificial layer, and avoids uneven subsequent reactions. Furthermore, the inert activation process preserves the amorphous state of the oxides, eliminating crack sources caused by unreduced oxide impurities, thus improving the fracture toughness of the material. The carbon layer formed by the glucose solution coating and synergistic segmented reaction vacuum hot-pressing sintering preferentially and completely reduces tungsten oxide to metallic tungsten, and simultaneously converts the aluminothermic reduction products into aluminum nitride nanoparticles through a carbothermic reaction. The invention eliminates the continuous brittle layer of alumina on the grain boundaries and also has a toughening effect by pinning grain boundaries and hindering crack propagation, further improving the fracture toughness of the material. Comparison of the wear resistance experimental data from the examples and comparative examples reveals that the uniform precursor sol in this invention avoids the agglomeration caused by traditional hydrolysis methods, ensuring the uniform composition of the subsequently generated high-entropy silicide reinforcing phase, resulting in good and consistent wear resistance. Simultaneously, the high-entropy silicide interconnects along the grain boundaries to form a load-bearing skeleton and guides titanium boride to grow into whiskers along specific crystal orientations of the matrix. These two elements work synergistically to effectively resist abrasive plowing, enhance the micro-area shear resistance, and endow the material with excellent wear resistance.
[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A method for preparing a wear-resistant titanium-aluminum alloy material, characterized in that, Includes the following steps: (1) Under a high-purity argon atmosphere, tetraethyl orthosilicate, tungsten acetylacetone, trimethyl borate, niobium ethanol and organic solvent A are mixed in a mass ratio of 1.5~2:0.5~1:0.8~1:0.5~0.6:10, and then 0.4~0.6 times the mass of tetraethyl orthosilicate stabilizer is added. The mixture is stirred at room temperature for 30 min to form solution A. At the same time, organic solvent B is dissolved in organic solvent A in a volume ratio of 2:5 and stirred evenly to obtain solution B. Under vigorous stirring, solution B is slowly added dropwise to solution A. After the addition is complete, the mixture is placed in a 40℃ water bath and stirred for 2 h to obtain a homogeneous precursor sol. (2) The pretreated titanium-aluminum pre-alloyed powder was placed in an argon atmosphere. The precursor sol, which was 2 to 3 times the mass of the titanium-aluminum pre-alloyed powder, was mixed with the powder spraying in three separate times. A uniform amorphous precursor gel film was built on the surface of each powder in a layer-by-layer accumulation manner. The powder was spread out and calcined in two steps. After cooling in the furnace, the self-made powder was obtained. (3) The self-made powder was sprayed into the self-made glucose solution under argon protection and slow stirring, stirred for 15 min, and vacuum dried at 60℃ for 2 h to obtain the self-made composite powder containing the carbon source precursor layer. It was loaded into a mold, pre-pressed into a blank, and calcined in a two-step activation atmosphere to obtain wear-resistant titanium-aluminum alloy material.
2. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The organic solvent A mentioned in step (1) is anhydrous ethanol.
3. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The stabilizer mentioned in step (1) is acetylacetone.
4. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The organic solvent B mentioned in step (1) is anhydrous propionic acid.
5. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The slow dripping rate in step (1) is 2 drops / s.
6. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The thickness of the amorphous precursor gel film in step (2) is 300~400nm.
7. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The thickness of the tiling in step (2) is 5mm.
8. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The homemade glucose solution in step (3) is prepared by weighing 5g of glucose and dissolving it in 50mL of deionized water, stirring magnetically until completely dissolved, and preparing a glucose aqueous solution with a mass fraction of 9%.
9. The wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The carbon source precursor layer in step (3) is a carbon source precursor layer with a thickness of 10 nm.
10. The application of the wear-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The mold mentioned in step (3) is a high-strength graphite mold with a boron nitride release agent uniformly coated on the inner wall.